Flaps on the Limbs - Dr. Mrs. Siti Roy Chowdhury (Indian Journal of Plastic Surgery)
Used for resurfacing defects of upper and lower limb have been discussed. Role of bridge flap to resurface fairly sizeable wound of the hand are discussed, also role of gastronaemius myocutaneus flap in resurfacing lower limb has been discussed in detail.